Combination of Genetic Manipulation Improved Saccharomycopsis fibuligera α-Amylase Secretion by Pichia pastoris - Shabarni Gaffar; Dessy Natalia; Toto Subroto; Oo Suprijana; Soetijoso Soemitro (Universitas Gadjah Mada, 2019)
This study assessed the combinations of genetic manipulation; signal peptide modification, gene dosage increment and co-expression of folding component, to increase Saccharomycopsis fibuligera R64 α-amylase (Sfamy) secretion in Pichia pastoris. Sfamy native signal peptide was replaced with modified signal peptide which contained 15 amino acid of mouse salivary α-amylase signal peptide fused to the pro-region of the signal peptide of Saccharomyces cerevisiae α-mating factor (α-MF). Increase in gene dosage was identified by screening for P. pastoris harboring multicopies of the Sfamy gene. Whereas, co-expression of folding component was done by addition of Protein Disulfide Isomerase (PDI). Expression plasmids harboring Sfamy containing modified signal sequence (pPICZA-MS-Sfamy) was used to transform P. pastoris GS115, and gene dosage increment was screened using zeocin. Effect of PDI co-expression on secretion levels of Sfamy was assessed by constructing the pPIC3.5K-Pdi1 plasmid and introducing into P. pastoris harboring multicopies of MS-Sfamy for expression of Sfamy. Signal peptide modification consequently increased Sfamy secretion by P. pastoris by 3.3-fold compared to native signal peptide. Gene dosage increment had improved Sfamy secretion by 11-fold in P. pastoris [MS-Sfamy] resistant to 2000 μg/mL zeocin, compared to P. pastoris harboring one copy of WT-Sfamy. Hence, PDI co-expression increased the secretion of Sfamy by 2-fold as compared without PDI co-expression. In summary, the combination of genetic manipulation successfully increased Sfamy secretion by 20-fold compared to P. pastoris harboring one copy of WT-Sfamy.